2019
DOI: 10.1371/journal.pone.0218391
|View full text |Cite
|
Sign up to set email alerts
|

Elsinochrome phytotoxin production and pathogenicity of Elsinoë arachidis isolates in China

Abstract: Peanut scab caused by Elsinoë arachidis is found throughout China’s peanut-growing areas. Elsinochrome produced by E . arachidis is a perylenequinone photosensitive mycotoxin vital to the pathogenic process of the pathogen. In this study, the complex mechanism underlying the regulation of elsinochrome biosynthesis by E . arachidis was investigated based on various nutritional and environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The biosynthesis of ESC in E. arachidis was signi cantly different in different light condition [47]. Under light condition, the production of ESC was 16 nmol/plug, while in the dark, no synthesis of toxins was detected.…”
Section: Rt-qpcr Analysis Of Escb1mentioning
confidence: 91%
See 1 more Smart Citation
“…The biosynthesis of ESC in E. arachidis was signi cantly different in different light condition [47]. Under light condition, the production of ESC was 16 nmol/plug, while in the dark, no synthesis of toxins was detected.…”
Section: Rt-qpcr Analysis Of Escb1mentioning
confidence: 91%
“…Elsinochrome was extraction and quantitative analysis as before [47]. To estimate the expression of ESCB1 transcripts at different light condition, the strain was cultured on PDA under dark conditions for 7 days, then take part to light condition for 48 h and isolated total RNA, respectively.…”
Section: Phylogenetic and Domain Analyses Of Fungal Polyketide Synthamentioning
confidence: 99%
“…ampelina are still unknown, many studies have shown that the elsinochromes produced by Elsinoe spp. are vital to the pathogenic process (Jiao et al, 2019 ; Liao & Chung, 2008 ; Wang et al, 2009 ). Elsinochromes, which are light‐dependent and nonhost‐selective phytotoxins, are structurally similar to the cercosporin phytotoxin (Yang & Chung, 2010 ).…”
Section: Genomics and Pathogenicity Of E Ampelinamentioning
confidence: 99%
“…Both metabolites are able to absorb light energy and can produce reactive oxygen species (ROS). A high amount of these toxins is reported to induce necrotic lesions on citrus and tobacco leaves [35][36][37]. 8,8′-bijuglone might exhibit similar functions in planta.…”
Section: Genome Analysis Of Z Pseudotsugaementioning
confidence: 99%